2003
DOI: 10.1038/nm971
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CNP in chondrocytes rescues achondroplasia through a MAPK-dependent pathway

Abstract: Achondroplasia is the most common genetic form of human dwarfism, for which there is presently no effective therapy. C-type natriuretic peptide (CNP) is a newly identified molecule that regulates endochondral bone growth through GC-B, a subtype of particulate guanylyl cyclase. Here we show that targeted overexpression of CNP in chondrocytes counteracts dwarfism in a mouse model of achondroplasia with activated fibroblast growth factor receptor 3 (FGFR-3) in the cartilage. CNP prevented the shortening of achond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
335
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(362 citation statements)
references
References 40 publications
22
335
0
1
Order By: Relevance
“…Interestingly, ERK1/2 MAP kinase activity is required for dephosphorylation of both p107 and p130, whereas p38 MAP kinase signaling is only necessary for dephosphorylation of p130 (Raucci et al, 2004). These data are in agreement with roles of both of these pathways in postmitotic chondrocytes (Zhen et al, 2000;Stanton et al, 2003;Murakami et al, 2004;Stanton et al, 2004;Yasoda et al, 2004). Furthermore, p107 dephosphorylation does not require transcription or translation, suggesting that it is independent of CKI induction, in contrast to p130 (Dailey et al, 2003).…”
Section: Function Of Cell-cycle Genes In the Growth Platesupporting
confidence: 74%
“…Interestingly, ERK1/2 MAP kinase activity is required for dephosphorylation of both p107 and p130, whereas p38 MAP kinase signaling is only necessary for dephosphorylation of p130 (Raucci et al, 2004). These data are in agreement with roles of both of these pathways in postmitotic chondrocytes (Zhen et al, 2000;Stanton et al, 2003;Murakami et al, 2004;Stanton et al, 2004;Yasoda et al, 2004). Furthermore, p107 dephosphorylation does not require transcription or translation, suggesting that it is independent of CKI induction, in contrast to p130 (Dailey et al, 2003).…”
Section: Function Of Cell-cycle Genes In the Growth Platesupporting
confidence: 74%
“…We have previously reported that BNP-Tg mice with higher copy numbers of the transgene show marked skeletal overgrowth [47], indicating that BNP likely activates the physiological CNP/GC-B pathway in the bone to stimulate endochondral ossification [48]. Therefore, it is important to clarify whether the beneficial effects of BNP observed in this study are GC-A-dependent or GC-B-dependent.…”
Section: Discussionmentioning
confidence: 78%
“…The anti-proliferative action of FGF 2 signaling in cartilage contrasts with the usual mitogenic response of cells to FGF stimulus (6), but the molecular basis of this paradox remains unclear. Recently, Erk MAP kinase was found as a candidate for FGFR3-mediated inhibition of chondrocyte proliferation and differentiation (7)(8)(9)(10).…”
mentioning
confidence: 99%